PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada PT. Tiki Jalur Nugraha Ekakurir (JNE) Cabang Medan Marelan) - Miryanda, Ade (MTU PRESS, 2023)
Customer loyalty is evidence that customers feel satisfied with a used product or service and make repeated purchases. This study aims to determine and analyze the effect of service quality, price, and location on customer loyalty. The method used in this study is a quantitative method with data collection techniques used in the form of primary data, where data is collected using a questionnaire. Conducting on customers who use JNE freight forwarding services as of February 2022 with a population of 3,328 customers with a sample of 100 respondents. The analysis results show that service quality, price and location partially have a positive and significant effect on customer loyalty at JNE branches of Medan Marelan. Then the analysis results prove that service quality, price and location simultaneously have a positive and significant effect on customer loyalty at JNE branch of Medan Marelan.